Parental Care System and Brood Size Drive Sex Difference in Reproductive Allocation: An Experimental Study on Burying Beetles - Wang, Wenxia; Ma, Long; Versteegh, Maaike A.; Wu, Hua; Komdeur, Jan (Frontiers in Ecology and Evolution, 2021)
Life-history theory predicts that increased resource allocation in current reproduction comes at the cost of survival and future reproductive fitness. In taxa with biparental care, each parent adjusts investment on current reproduction according to changes in their partner’s effort, but these adjustments may be different for males and females as they may have different reproductive strategies. Numerous theoretical and empirical studies have proposed the mechanism underlying such adjustments. In addition, the value of the brood or litter (brood size) has also been suggested to affect the amount of care through manipulation of brood size. While the two conditions have been studied independently, the impact of their interplay on potential sex-dependent future reproductive performance remains largely unknown. In this study, we simultaneously manipulated both care system (removal of either parent vs no removal) and brood size to understand their joint effect on reproductive allocation and trade-off between current and future reproduction. Our results show that males compensated for mate loss by significantly increasing the level of care regardless of brood size, while females exhibited such compensation only for small brood size. Additionally, with an increase in allocation to current reproduction, males showed decreased parental investment during the subsequent breeding event as a pair. These findings imply a dual influence of parental care system and brood size on allocation in current reproduction. Moreover, the impact of such adjustments on sex-dependent differences in future reproductive fitness (parental care and offspring fitness) is also demonstrated. Our findings enhance the understanding of sex roles in parental investment and highlight their importance as drivers of reproductive allocation.